Geriatrician interventions on medication prescribing for frail older people in residential aged care facilities - Poudel A (Dove Medical Press, 2015)
Arjun Poudel,1 Nancye M Peel,2 Charles A Mitchell,1 Leonard C Gray,2 Lisa M Nissen,1,3 Ruth E Hubbard21School of Pharmacy, 2Centre for Research in Geriatric Medicine, The University of Queensland, 3School of Clinical Sciences, Queensland University of Technology, Brisbane, QLD, AustraliaObjective: In Australian residential aged care facilities (RACFs), the use of certain classes of high-risk medication such as antipsychotics, potent analgesics, and sedatives is high. Here, we examined the prescribed medications and subsequent changes recommended by geriatricians during comprehensive geriatric consultations provided to residents of RACFs via videoconference.Design: This is a prospective observational study.Setting: Four RACFs in Queensland, Australia, are included.Participants: A total of 153 residents referred by general practitioners for comprehensive assessment by geriatricians delivered by video-consultation.Results: Residents’ mean (standard deviation, SD) age was 83.0 (8.1) years and 64.1% were female. They had multiple comorbidities (mean 6), high levels of dependency, and were prescribed a mean (SD) of 9.6 (4.2) regular medications. Ninety-one percent of patients were taking five or more medications daily. Of total medications prescribed (n=1,469), geriatricians recommended withdrawal of 9.8% (n=145) and dose alteration of 3.5% (n=51). New medications were initiated in 47.7% (n=73) patients. Of the 10.3% (n=151) medications considered as high risk, 17.2% were stopped and dose altered in 2.6%.Conclusion: There was a moderate prevalence of potentially inappropriate high-risk medications. However, geriatricians made relatively few changes, suggesting either that, on balance, prescription of these medications was appropriate or, because of other factors, there was a reluctance to adjust medications. A structured medication review using an algorithm for withdrawing medications of high disutility might help optimize medications in frail patients. Further research, including a broader survey, is required to understand these dynamics.Keywords: frail older, geriatrician intervention, high-risk medications, residential aged care facilities